2020
DOI: 10.1055/a-1216-9928
|View full text |Cite
|
Sign up to set email alerts
|

Transoral endoscopic ultrasound-guided fine-needle biopsy of a tumor of the parapharyngeal space

Abstract: ▶ Fig. 3 EUS image of a tumor of the right parapharyngeal space located between the pharyngeal wall, the medial pterygoid muscle (mpm), and the ramus of the mandible. The tumor (TU) is 34 mm × 28 mm in size, has well-delineated borders and a hypoechoic, homogeneous echo pattern. A needle passing through the pharyngeal wall into the tumor is visible. ▶ Fig. 4 Specimen obtained by EUS-guided fine-needle biopsy under 100 × magnification. Typical appearance of a pleomorphic adenoma of the parotid gland with epithe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Another important finding is the excellent diagnostic accuracy of preoperative FNAB in our series: as it was demonstrated in previous papers, 58,59 the accuracy of core biopsy is much higher than simple cytological sampling and we believe FNAB should be regarded as the gold standard even when performed transorally. Interestingly, a very recent paper has also shown that PPSTs can be efficiently biopsied using a flexible gastrointestinal echoendoscope 60 . However, the role of preoperative FNAB is still controversial with a high rate of the nondiagnostic procedure, even when the needle is CT‐guided 61 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another important finding is the excellent diagnostic accuracy of preoperative FNAB in our series: as it was demonstrated in previous papers, 58,59 the accuracy of core biopsy is much higher than simple cytological sampling and we believe FNAB should be regarded as the gold standard even when performed transorally. Interestingly, a very recent paper has also shown that PPSTs can be efficiently biopsied using a flexible gastrointestinal echoendoscope 60 . However, the role of preoperative FNAB is still controversial with a high rate of the nondiagnostic procedure, even when the needle is CT‐guided 61 .…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a very recent paper has also shown that PPSTs can be efficiently biopsied using a flexible gastrointestinal echoendoscope. 60 However, the role of preoperative FNAB is still controversial with a high rate of the nondiagnostic procedure, even when the needle is CT‐guided. 61 Among studies included in the present paper, three of seven debate the role of preoperative biopsy and only one author shows their own results with FNAC: preoperative cytological analysis rendered a histopathological diagnosis that was the same as the final examination in two of three patients (66.7%), while one patient did not undergo the procedure because of the benign nature of the lesion suggested by MRI.…”
Section: Discussionmentioning
confidence: 99%
“…ere are many kinds of tumors in PSS, with more than 70 kinds, but benign tumors account for 70-80%, malignant tumors account for 20-30%, including primary tumors, direct spread tumors, and distant metastatic tumors. It is recognized that the more common PSS tumors are pleomorphic adenoma, schwannoma, and paraganglioma [2,3]. Considering the concealment of PSS, it is often di cult to detect PSS tumors in the early stage.…”
Section: Introductionmentioning
confidence: 99%